PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN RESTORAN BARUNA SANUR - Inten Surya Utami, Ida Ayu; Jatra, I Made (E-Jurnal Manajemen; Vol 4 No 7 (2015), 2015)
Purpose of this study for examine and analyze 1) the influence of the quality of service that consists of physical evidence, reliability, responsiveness, assurance and empathy for customer satisfaction Baruna Sanur Restaurant. 2) The difference between customer satisfaction of men with female customers. Design research using associative method. These samples included 115 who were taken using purposive sampling technique. Data were analyzed by multiple linear regression and Man - Whitney Results analysis of the data shows that overall service quality variables (tangibles, reliability, responsiveness, assurance, and empathy) and a significant positive effect on customer satisfaction Baruna Sanur Restaurant, where there is customer satisfaction differences between men and women to the service of Baruna Sanur Restaurant. The implications of this research, Sanur Restaurant Baruna more attention on the five dimensions of service quality, especially in terms of responsiveness that customer satisfaction is met according to the desired expectations
Keywords: Physical Evidence, Reliability, Responsiveness, Assurance, Empathy, Customer Satisfaction